Mechanistic Study of Bakuchiol-Induced Anti-breast Cancer Stem Cell and in Vivo Anti-metastasis Effects - Li, Li; Liu, Chi C.; Chen, Xueping; Xu, Shisan; Hernandez Cortes-Manno, Sinai; Cheng, Shuk H. (Frontiers in Pharmacology, 2017)
Cancer stem cells are involved in cancer establishment, progression, and resistance to current treatments. We demonstrated the in vitro and in vivo anti-breast cancer effect of bakuchiol in a previous study. However, the ability of bakuchiol to target breast cancer stem cells (BCSCs) and inhibit breast cancer metastasis remains unknown. In the current study, we used the cell surface markers CD44 and CD24 to distinguish BCSCs from MCF-7 cells. Bakuchiol inhibited mammosphere formation and aldehyde dehydrogenase (ALDH) activity in BCSCs. Moreover, bakuchiol induced apoptosis and suppressed the mitochondrial membrane potential of BCSCs. Bakuchiol upregulated the expression levels of pro-apoptotic genes, BNIP3 and DAPK2. Bakuchiol induced oxidative stress and altered lipogenesis in BCSCs. In zebrafish xenografts, bakuchiol inhibited breast cancer cell metastasis in vivo. In addition, bakuchiol altered the expression levels of metastasis-related genes through upregulating CK18 and downregulating Notch3, FASN, TGFBR1, and ACVR1B. Our study provides evidence for the anti-breast cancer potential of bakuchiol.